Factors associated with shock-refractory prehospital cardiac arrest - Kyung Hun Yoo; Byuk Sung Ko; Won Young Kim; Tae Ho Lim; Hyunggoo Kang; The Korean Cardiac Arrest Resuscitation Consortium (Scientific Reports)
Abstract A significant number of out-of-hospital cardiac arrest (OHCA) patients experience refractory ventricular arrhythmias despite prompt defibrillation. These refractory arrhythmias are associated with poor clinical outcomes, underscoring the need to investigate improved management strategies. Therefore, this study aimed to identify factors associated with shock-refractory OHCA during the prehospital stages of resuscitation. This multicenter observational study included adult OHCA patients (age ≥ 18 years) from October 2015 to June 2022 who required at least one prehospital defibrillation. This study’s primary endpoint was shock-refractory OHCA, defined as three defibrillation shocks during resuscitation. A logistic regression analysis was performed to identify factors associated with shock-refractory OHCA. Among the 4320 patients included, 1961 (45.4%) experienced shock-refractory OHCA. Male sex (adjusted odds ratio [aOR], 1.423; 95% confidence interval [CI], 1.209–1.676), bystander automated external defibrillator (AED) shock (OR 2.350; 95% CI 1.426–3.968), and initial shockable rhythm (OR 1.739; 95% CI 1.490–2.030) were associated with a high risk of shock-refractory, while old age (OR 0.993; 95% CI 0.989–0.998) and receive bystander cardiopulmonary resuscitation (CPR) (OR 0.829; 95% CI 0.718–0.958) were associated with a low risk of shock-refractory OHCA. This study showed that the prehospital factors of age, sex, initial rhythm, AED shock source, and absence of bystander CPR were associated with shock-refractory OHCA.